PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK BERBASIS REALISTIC MATHEMATIC EDUCATION TERHADAP HASIL BELAJAR SISWA - Raden Zikry Amar; Ali Usmar; Betri Wendra (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study discusses the effect of using Student Worksheets based on Realistic Mathematic Education (RME) on student learning outcomes at MTs Jauharul Iman, Senaung Muaro Village, Jambi on the subject of the Pytagoras Theorem. This study aims to determine whether the use of RME-based LKPD can improve student learning outcomes. This research is a quantitative study using the Quasi Experimental Design method with the research design Nonequivalent Control Group Design. The sampling technique used random sampling by taking all the population into a sample, where class VIII A consisted of 19 students as the control class and class VIII B had 19 students as the experimental class. The data collection technique was carried out using a multiple-choice test totaling 16 questions. The analysis in this study used the t_test test and the phi correlation test. From the results of the ttest test at the dan  significance levels, it was found that . Because  and from the results of the analysis at the significance level of dan  it was obtained  because    was rejected, meaning that there was a significant effect between student learning outcomes in the experimental class and the control class. Thus, it can be concluded that the learning outcomes of students who use the RME-based LKPD are better than the learning outcomes of students who use Scientific-based LKPD